Competition and Competitiveness in Lithuanian Agriculture - Poviliūnas, Antanas (Ekonomika, 2001)
The paper deals with three types of competition. The advantage of agri-food market in generic competition is to meet physiological needs of consumers. In 1999 inhabitants of Lithuania spent about a half of total expenditure for food. While income increased the percentage spent for food dropped, but locally expenditure went up. In the first decile expenditure for food, beverages and tobacco made up 71% of total expenditure, but in the tenth decile they came down to 34%. However, total expenditure increased by 3,9 times. Product class competition is intercompetition of separate foodstuffs. Consumer purchasing power, nutrition habits and changes due to market globalization have influence on this competition. In 1990-1999 consumption of vegetable oils and margarine increased by 71% while consumption of fats, including butter, decreased. Because of market globalization, the markets of fruit, berries and vegetables became more important to people nutrition. In 1999 consumption of dairy products made up only 42% of the 1990 consumption level, that of eggs - SS%, meat products - about 60%. Brand competition enriches assortment of separate foodstuffs. However, to determine impact of competition types on agri-food markets is hardly possible. Actually agri-producers know only the fact that competition is going strengthen both in domestic and foreign markets, and their main concern is 10 increase competitiveness of their farm.The possibilities to increase competitiveness in Lithuania are limited by the area of profitable agri-business. Therefore, under market conditions it is important to know areas of non-productive and lowproductive land, their distribution, to foresee prospects of their use.In Lithuania are clear tendencies of farm enlargement; formation of land market is going more rapid. Land lease has a crucial importance to farm enlargement. In farms up to 10 ba the area of leased land makes up 29%, in farms over 150 ha - 83%. In the farms, which average size fluctuates about 256 ba, the area of own land makes up 31 ba and the area of leased land comes 10 212 ha or is 6,8 limes larger. This shows that leased land can gel into land market primarily. The main question is, whether actual land users will have capital 10 buy it. Land market is slack because local farmers have no funds 10 buy land. Mean while, the law forbids buying land for legal persons and foreigners. When this prohibition will he abolished, land purchase can be limited by economic land value, some political motives.Orientation towards the increase of farm production capacities is limited by a lack of initial capital and, in some cases. personal initiative. Competence to farm under new conditions and personal initiative are characterized by farmers’ age. active participation in farmers’ organisations, and application of farming experience of foreign countries. Research results show, that although hardly and slowly but certain outlines for competitive farm in Lithuanian agriculture are developing.